Pengaruh Kompensasi, Beban Kerja, Dan Stress Kerja Terhadap Kepuasan Kerja Pegawai Dinas Perpustakaan Dan Kearsipan Provinsi Banten - Ningrum, Lathifah Indah Cahya; Prihatma, Gugup Tugi (Jurnal Akuntansi Manajemen (JAKMEN), 2024)
The purpose of this study was to determine the effect of compensation, workload and job stress on job satisfaction of Banten Province Library and Archives Office employees. The research method used is quantitative method. The results of the research on the compensation variable on the job satisfaction variable show the t value greater than the t table (4,016> 1,984), the workload variable on the job satisfaction variable shows the t value smaller than the t table (1,591 < 1,984), the work stress variable on the job satisfaction variable shows the t value greater than the t table (3,072> 1,984), and the f test which shows a significance value of 0,00 smaller than 0,05 and the f count is greater than the f table (55,180> 2,70). The results of the study indicate that compensation has an influence on job satisfaction in Banten Provincial Library and Archives Service employees, workload does not affect job satisfaction in Banten Provincial Library and Archives Service employees, job stress affects job satisfaction in Banten Provincial Library and Archives Service employees, compensation, workload, and job stress simultaneously affect job satisfaction at the Banten Provincial Library and Archives Service.